Accuracy and precision of CPET equipment: A comparison of breath-by-breath and mixing chamber systems. (January 2013) - Beijst, Casper; Schep, Goof; Breda, Eric van; Wijn, Pieter F. F.; Pul, Carola van
<x xml:space="preserve">Abstract</x> Cardiopulmonary exercise testing (CPET) has become an important diagnostic tool for patients with cardiorespiratory disease and can monitor athletic performance measuring maximal oxygen uptake <inline-graphic xlink:href="ark:/27927/pgg1mqcfvvs" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Vo2; max. The aim of this study is to compare the accuracy and precision of a breath-by-breath and a mixing chamber CPET system, using two methods. First, this study developed a (theoretical) error analysis based on general error propagation theory. Second, calibration measurements using a metabolic simulator were performed. Error analysis shows that the error in oxygen uptake (<inline-graphic xlink:href="ark:/27927/pgg1mqcfw35" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Vo2) and carbon dioxide production (Vco2<inline-graphic xlink:href="ark:/27927/pgg1mqcftkv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) is smaller for mixing chamber than for breath-by-breath systems. In general, the error of the flow sensor <inline-graphic xlink:href="ark:/27927/pgg1mqcfwkw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />δV, the error in temperature of expired air δTB and the delay time error δtdelay are significant sources of error. Measurements using a metabolic simulator show that breath-by-breath systems are less stabile for different values of minute ventilation than mixing chamber systems.